Performance of Broilers Fed Varying Levels of Palm Kernel Cake - Bello, K.M.; Oyawoye, E.O.; Bogoro, S.E.; Dass, U.D. (International Journal of Poultry Science, 2011)
The high cost of conventional feed ingredients has necessitated the investigation into unconventional readily available feedstuffs such as Palm Kernel Meal (PKM). The study was conducted to determine the effect of using different levels of PKM in broilers chicks diet on performance, cost effectiveness, blood chemistry and carcass characteristics. Two hundred (200) day old Anak 2000 broiler chicks were in a completely randomized design allocated to five dietary treatments (0, 10, 20, 30 and 40% PKM) in four replicates. The birds were fed isonitrogenous and isocaloric diets containing 21% crude protein and 2700 kcal/kgME at the starter phase and 23% CP and 3000 kcal/kgME for the Finisher phase. The result showed that the feed intake and daily weight gain increases significantly (p